Isolated Epithelial Cells of the Toad Bladder : Their preparation, oxygen consumption, and electrolyte content - Gatzy, J. T. (The Rockefeller University Press, 1968)
Epithelial cells of the toad bladder were disaggregated with EDTA, trypsin, hyaluronidase, or collagenase and were then scraped free of the underlying connective tissue. In most experiments EDTA was complexed with a divalent cation before the tissue was scraped. Q (O(O2)), sucrose and inulin spaces, and electrolytes of the isolated cells were measured. Cells disaggregated by collagenase or hyaluronidase consumed O(2) at a rate of 4 µl hr(-1) dry wt(-1). Q (O(O2)) was increased 50% by ADH (100 U/liter) or by cyclic 3',5'-AMP (10 mM/liter). Na(+)-free Ringer's depressed the Q (O(O2)) by 40%. The Q (O(O2)) of cells prepared by trypsin treatment or by two EDTA methods was depressed by Na(+)-free Ringer's but was stimulated relatively little by ADH. Two other EDTA protocols produced cells that did not respond to Na(+) lack or ADH. The intracellular Na(+) and K(+) concentrations of collagenase-disaggregated cells were 32 and 117 mEq/kg cell H(2)O, respectively. Cation concentrations of hyaluronidase cells were similar, but cells that did not respond to ADH had higher intracellular Na(+) concentrations. Cells unresponsive to ADH and Na(+) lack had high sucrose spaces and low transcellular membrane gradients of Na(+), K(+), and Cl(-). The results suggest that trypsin and EDTA disaggregation damage the active Na(+) transport system of the isolated cell. Certain EDTA techniques may also produce a general increase in permeability. Collagenase and hyaluronidase cells appear to function normally.